Do consumer attitudes matter in capital markets? A study of mutual funds in Oman market - Arshi A. Tahseen; Surya Narayana (Journal of Finance and Investment Analysis, 2012)
The financial sector particularly the mutual funds in Oman market have shown limited potential to attract consumers. Consumer attitudes towards financial investments have always been a challenge for the finance companies due to limited risk appetite of consumers which are largely attributed to both cognitive and affective components of attitude. Through a process of methodological triangulation data was collected from experts in the finance sector from a sample of 200 consumers. Pearson product moment correlation and standard multiple regressions through SPSS version 20 were used to study the hypothesized relationships in this study. This study throws light on critical variables that shape consumer attitudes towards mutual funds and recommends the scope for introducing new mutual funds which has significant implications on capital markets in Oman.
Keywords: G1; G11; G14; 330; mutual funds; investor; consumer attitudes; behavior; cognition; affect; fund performance; brand image; net asset value; capital market authority